Neglected pollinator syndromes in seasonally inundated Renosterveld - Goldberg, Karen (Department of Biological Sciences, 2018)
A range of fairly common plants were investigated in Darling in the Western Cape, to determine their pollinator syndromes, and to evaluate the relative importance of monkey beetles (Scarabaeidae: Rutelinae: Hopliini) and relatively short-tongued horseflies (Tabanidae) in their pollination. Detailed observations showed that all the plants investigated are visited by more than one insect species. Visitation rates and pollen loads of all insects found on the plants were used to assess their pollination efficiency. For all plants investigated, only a subset of the visitor-suite was found to contribute to the plant's reproductive success. Geissorhiza radians (Thunb.) Goldblatt and Wachendorfia paniculata L. seem to have specialized pollinator systems, both relying on tabanids for their pollination, while Heliophila coronipifolia, L. Monsonia speciosa, L.f. Ornothogalum thyrsoides, Jacq. Romulea hirsuta (Klatt) Baker and Ursinia anthemoides (L.) Poir. appear to have more generalized pollinator syndromes. Monkey beetles were the predominant and generally the most efficient pollinators for all these species. It is therefore concluded that these two insect groups are important pollinators of the plants investigated and probably play a part in the pollination of several other plants in the community. An evaluation of the larval requirements of pollinators revealed that although some species show clear patterns in terms of what types of soil conditions they prefer, successful emergence of insect species is generally not limited by a shortage of suitable habitats. Environmental variability may therefore play the largest role in determining the emergence and abundance of pollinators. This has implications for plants reliant on insects for their pollination, especially for species with specialized pollinator syndromes. Fluctuations in the environment may be a partial explanation for the prevalence of the generalized pollination syndromes observed.